Expression of inhibitory receptors on peripheral blood T cells in pregnant women with preeclampsia - E. A. Smetanenko; N. A. Khonina; O. Y. Leplina; M. A. Tikhonova; E. V. Batorov; N. M. Pasman; E. R. Chernykh (Медицинская иммунология, 2023)
Maternal adaptation of the immune system aimed at limiting the immune response to fetal antigens is a necessary condition for a successful pregnancy. It involves various mechanisms (Th1/Th2 switching, Treg expansion, induction of anergy and apoptosis of T lymphocytes, development of T cell depletion) that are induced through the ligation of inhibitory receptors. Accordingly,  the expression of inhibitory receptors on  T cells, including PD-1, CTLA-4, and Tim-3 molecules, may reflect the effectiveness of immune adaptation and its impairment in pregnancy pathology. Preeclampsia (PE), the pathogenesis of which is associated with the impairments of immunological tolerance is a major complication of pregnancy. Accordingly, changes in the expression of inhibitory receptors on T cells may be biomarkers of abnormal gestation and potential therapeutic targets. The aim of this work was to study the expression of inhibitory molecules on peripheral blood T cells in women with PE. The study recruited 29 pregnant women with PE and 36 women with uncomplicated pregnancies in the second half of pregnancy. Pregnant women of the study groups were comparable in terms of gestational age, number of pregnancies and parity of childbirth. The control group consisted of 28 fertile women with children. Relative content of CD8+PD-1+, CD8+CTLA-4+, CD8+TIM-3+, CD8+PD-1+TIM-3+, CD4+PD-1+, CD4+CTLA-4+, CD4+TIM-3+, CD4+PD-1+TIM-3+T cells in blood were analyzed  by  flow cytometry. It has been shown that uncomplicated pregnancy is associated with increased expression of PD-1 and Tim-3 T cells, which is manifested by an increase in the relative content of CD4+Tim-3+, CD8+PD-1+ and PD-1+Tim-3+T lymphocytes . In PE, on the contrary, there is a reduction in the expression of PD-1 and Tim-3 by T cells, in particular, a decrease in the proportion of CD4+Tim-3+ and CD8+PD-1+ cells; the absence of elevated levels in PD-1+Tim-3+ cells (compared to uncomplicated gestation) and an increase in CTLA-4+ cells within CD4+ lymphocytes. Changes in the expression of inhibitory receptors are associated with the severity of PE. A decrease in CD4+Tim-3+ and CD8+PD-1+T cells is most typical for patients with moderate PE, and an increase in CD4+CTLA-4T cells for pregnant women with severe PE. The relationship between changes in the expression of inhibitory molecules and the onset of PE has also been demonstrated. A distinctive feature of early PE is a decrease in the proportion of CD8+CTLA-4+ cells and a more pronounced increase in CD4+CTLA-4+ cells, while late PE is associated with a decrease in CD4+PD-1+ cells and a more pronounced decrease in CD4+Tim-3+ cells. The results obtained indicate a changes in the expression of CTLA-4, PD-1 and Tim-3 molecules on circulating T cells in pregnant women with PE and the association of these changes with the severity and the onset of PE manifestation.